2021
DOI: 10.7759/cureus.16332
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sacubitril/Valsartan Versus Enalapril in the Management of Heart Failure

Abstract: Background and objectiveThe recent emergence of new molecules like angiotensin receptor-neprilysin inhibitor (ARNI) has highlighted the need for an update in heart failure (HF) management, as they have proven to yield better patient outcomes compared to the traditional angiotensin-converting enzyme inhibitor/angiotensin II receptor blocker (ACEI/ARB) use. This study aimed to compare HF-related hospitalization and death in patients on either ACEI/ARBs or ARNI in a local setting. MethodsThis two-arm intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The mean duration of this trial was 22 months The other 5 smaller comparative trials showed no superiority of SV over either enalapril/ramipril/valsartan in terms of either total or cardiovascular mortality. [10][11][12][13][14] Regarding hospitalization rate for heart failure, the data were not consistent. Two of these trials showed no differences between groups, while 3 did in favor of SV.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The mean duration of this trial was 22 months The other 5 smaller comparative trials showed no superiority of SV over either enalapril/ramipril/valsartan in terms of either total or cardiovascular mortality. [10][11][12][13][14] Regarding hospitalization rate for heart failure, the data were not consistent. Two of these trials showed no differences between groups, while 3 did in favor of SV.…”
Section: Resultsmentioning
confidence: 88%
“…Since the publication of PARADIGM HF, 6 other comparative trials have been published that reports hard endpoints. [9][10][11][12][13][14] The largest is the PARADISE MI trial, which compared SV 97/103 mg twice a day to ramipril 5 mg twice a day in 5661 patients who had a recent myocardial infarction, reduced ejection fraction, and/or heart failure symptoms. 9 Unlike PARADIGM HF, there were no differences in total or cardiovascular mortality or rate of hospitalizations for heart failure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we included data from 34 studies satisfying the inclusion criteria (Fig. 1 ) [ 22 – 55 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%